Advancing the Understanding of Acupoint Sensitization and Plasticity Through Cutaneous C-Nociceptors - Cui, Xiang; Liu, Kun; Gao, Xinyan; Zhu, Bing (Frontiers in Neuroscience, 2022)
Acupoint is the key area for needling treatment, but its’ physiology is not yet understood. Nociceptors, one of the responders in acupoints, are responsible for acupuncture manipulation and delivering acupuncture signals to the spinal or supraspinal level. Recent evidence has shown that various diseases led to sensory hypersensitivity and functional plasticity in sensitized acupoints, namely, acupoint sensitization. Neurogenic inflammation is the predominant pathological characteristic for sensitized acupoints; however, the underlying mechanism in acupoint sensitization remains unclear. Recent studies have reported that silent C-nociceptor (SN), a subtype of C nociceptors, can be “awakened” by inflammatory substances released by sensory terminals and immune cells under tissue injury or visceral dysfunction. SN can transform from a mechano-insensitive nociceptors in a healthy state to a mechanosensitive nociceptors. Activated SNs plays a vital in sensory and pain modulation, and can amplify sensory inputs from the injured tissue and then mediating sensory hyperalgesia. Whether activated SN is involved in the mechanism of acupoint sensitization and contribute to the delivery of mechanical signals from needling manipulation remains unclear? In this review, we discuss the known functions of cutaneous C nociceptors and SNs and focus on recent studies highlighting the role of activated SNs in acupoint functional plasticity.